Can G-quadruplex become a promising target in HBV therapy? - Teng, Ye; Zhu, Ming; Chi, Yuan; Li, Lijing; Jin, Ye (Frontiers in Immunology, 2022)
The chronic infection with hepatitis B virus (HBV) is an important health problem that affects millions of people worldwide. Current therapies for HBV always suffer from a poor response rate, common side effects, and the need for lifelong treatment. Novel therapeutic targets are expected. Interestingly, non-canonical structures of nucleic acids play crucial roles in the regulation of gene expression. Especially the formation of G-quadruplexes (G4s) in G-rich strands has been demonstrated to affect many bioprocesses including replication, transcription, and translation, showing great potential as targets in anticancer and antiviral therapies. In this review, we summarize recent antiviral studies about G4s and discuss the potential roles of G4 structures in antiviral therapy for HBV.